Students’ personality factors as correlates of academic performance among gifted underachievers in selected secondary schools in Ibadan (2016)
The study investigated students' personality factors as correlates of academic performance among gifted underachievers in selected secondary school in Ibadan, Nigeria. It examined the relationship between the students' personality and their academic performance especially gifted underachievers. The population consisted of gifted underachievers in selected senior secondary schools in Ibadan. A total sample of 100 gifted under achieving students were randomly selected from five out of eleven local government areas in Ibadan. A validated instrument titled International Personality Item Pool was used to elicit information from the students. Results showed that conscientiousness, extraversion, neuroticism, agreeableness, and openness jointly predict students' academic performance (p<0.05). This implied that when these five variables jointly influence students' academic performance. Openness was highly significant (t 6.880; p<0.05) and affect students' academic performance. However, there are no significant relationship between neuroticism and students' academic performance; extraversion and students' academic performance; agreeableness and students' academic performance; and conscientiousness and students' academic performance, (p> 0.05).